2014
DOI: 10.1371/journal.pone.0088414
|View full text |Cite
|
Sign up to set email alerts
|

Infrared-Transparent Gold Nanoparticles Converted by Tumors to Infrared Absorbers Cure Tumors in Mice by Photothermal Therapy

Abstract: Gold nanoparticles (AuNPs) absorb light and can be used to heat and ablate tumors. The “tissue window” at ∼800 nm (near infrared, NIR) is optimal for best tissue penetration of light. Previously, large, 50–150 nm, gold nanoshells and nanorods that absorb well in the NIR have been used. Small AuNPs that may penetrate tumors better unfortunately barely absorb at 800 nm. We show that small AuNPs conjugated to anti-tumor antibodies are taken up by tumor cells that catalytically aggregate them (by enzyme degradatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
54
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(55 citation statements)
references
References 36 publications
1
54
0
Order By: Relevance
“…following treatment and to a one year survival rate of 50-86%, higher than that of 0-20% observed for a treatment with radiation alone, (80)(81)(82). NIR heating of AuNPs in mice with squamous carcinoma showed tumour disappearance after three days, (83). It was also demonstrated that NIR absorption of light is 100 000 higher with AuNPs than with standard fluorophores, (83).…”
Section: I3 Metallic Nanoformulationmentioning
confidence: 97%
See 1 more Smart Citation
“…following treatment and to a one year survival rate of 50-86%, higher than that of 0-20% observed for a treatment with radiation alone, (80)(81)(82). NIR heating of AuNPs in mice with squamous carcinoma showed tumour disappearance after three days, (83). It was also demonstrated that NIR absorption of light is 100 000 higher with AuNPs than with standard fluorophores, (83).…”
Section: I3 Metallic Nanoformulationmentioning
confidence: 97%
“…NIR heating of AuNPs in mice with squamous carcinoma showed tumour disappearance after three days, (83). It was also demonstrated that NIR absorption of light is 100 000 higher with AuNPs than with standard fluorophores, (83).…”
Section: I3 Metallic Nanoformulationmentioning
confidence: 99%
“…Since solid spherical AuNPs do not absorb significantly at 800 nm, another approach is to have tumor cells take them up and aggregate them in endosomes and lysosomes 2022 . When AuNPs aggregate, their absorption spectrum red-shifts 23, 24 , which can be into the NIR.…”
Section: Introductionmentioning
confidence: 99%
“…When AuNPs aggregate, their absorption spectrum red-shifts 23, 24 , which can be into the NIR. The advantages of using small AuNPs (e.g., 1–20 nm), compared to nanoshells (~130 nm) and nanorods (~50 nm) might be: a) better penetration into tumors 22, 25–28 , and b) lower background absorption in non tumor cells and blood that do not aggregate the AuNPs (i.e., the small AuNPs ideally only aggregate and become NIR absorptive in the tumor while background amounts in normal tissue are unaggregated and NIR transparent and do not contribute to heating compared to NPs that are preformed to absorb NIR wherever they are).…”
Section: Introductionmentioning
confidence: 99%
“…Other researchers demonstrated that formulations of AuNPs functionalized with Erbitux (an anti-epidermal growth factor receptor antibody) lead to targeted endosome and lysosome delivery. 54 The present study relies on apoE3-mediated lipoprotein uptake mechanism adopted by cells to process the rHDL-AuNP.…”
mentioning
confidence: 99%